2018
DOI: 10.3389/fphys.2018.00456
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Olfactory Receptor OR10H1 in Human Urinary Bladder Cancer

Abstract: Olfactory receptors (ORs) are a large group of G-protein coupled receptors predominantly found in the olfactory epithelium. Many ORs are, however, ectopically expressed in other tissues and involved in several diseases including cancer. In this study, we describe that one OR, OR10H1, is predominantly expressed in the human urinary bladder with a notably higher expression at mRNA and protein level in bladder cancer tissues. Interestingly, also significantly higher amounts of OR10H1 transcripts were detectable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 67 publications
1
44
1
Order By: Relevance
“…PSGR/OR51E2 expression levels have been found to correlate with prognosis (Cao et al, 2015 ), and a mouse model of PSGR/OR51E2 overexpression suggests that this receptor does indeed play a role in tumor development (Rodriguez et al, 2014 ). There is also one report that the closely related receptor OR51E1 also inhibits growth of prostate cancer cells (Maßberg et al, 2016 ) and another that OR10H1 plays a potential role in bladder cancer (Weber et al, 2018 ). Finally, it has also been shown that ORs are expressed in the kidney and play functional roles in renal function.…”
Section: Olfactory Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…PSGR/OR51E2 expression levels have been found to correlate with prognosis (Cao et al, 2015 ), and a mouse model of PSGR/OR51E2 overexpression suggests that this receptor does indeed play a role in tumor development (Rodriguez et al, 2014 ). There is also one report that the closely related receptor OR51E1 also inhibits growth of prostate cancer cells (Maßberg et al, 2016 ) and another that OR10H1 plays a potential role in bladder cancer (Weber et al, 2018 ). Finally, it has also been shown that ORs are expressed in the kidney and play functional roles in renal function.…”
Section: Olfactory Receptorsmentioning
confidence: 99%
“…OR51E1 also has been reported to inhibit prostate cancer cell growth (Maßberg et al, 2016 ). In addition, OR2J3 activation induced apoptosis and inhibited cell proliferation in a non-small-cell lung cancer cell line (Kalbe et al, 2017 ); OR51B4 activation was found to have anti-proliferative, anti-migratory, and pro-apoptotic effects in colorectal cancer (Weber et al, 2017 ); and OR10H1 has been reported to play a role in bladder cancer (Weber et al, 2018 ).…”
Section: Therapeutic Potentialmentioning
confidence: 99%
“…Interestingly, in addition to their reported expression in the healthy tissues, the past literature also offers a number of independent anecdotes linking elevated expression of specific ORs with the molecular prognosis of specific cancers 23 , 24 , 27 , 33 , 36 , 43 . Such examples include OR51B5 and OR2AT4 in leukemia 55 , OR7C1 in colorectal cancer 35 , OR51E2 in melanoma 32 , OR10H1 in bladder cancer 56 , OR51E2 in prostate cancer 31 , OR51E1 in small intestine cancer 34 , and OR2B6 in breast carcinoma 23 , 43 . Interestingly, the functional validations involving ligand-mediated activation of the aforementioned cancer-associated ORs resulted in a decrease in cancer cell proliferation or the complete cessation of the cancer growth, which further suggests their importance in clinical setups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the previously described compartments of Basal-like tumor, Classical tumor, Activated stroma, Normal stroma, immune, endocrine and exocrine, we also identified two new compartments, which we annotated as olfactory and histone. Interestingly, a study has associated the olfactory transduction pathway with pancreatic cancer risk 27 , and additional studies have shown the overexpression of olfactory receptors in multiple cancer types, including prostate 28,29 , bladder 30 and breast 31 cancers. In agreement with these studies, we found that our olfactory compartment was indeed present in prostate adenocarcinoma (PRAD), bladder urothelial carcinoma (BLCA), as well as several other cancer types (Supplementary Data 1).…”
Section: Discussionmentioning
confidence: 99%